Medical Confidentiality in an Expertise - Gündoğmuş, Ümit Naci (The Bulletin of Legal Medicine, 2001)
While preparing a forensic medicine expertise, the one of the most frequently encountered ethical problem is the one in which medical confidentiality is concerned. For example, if an information that should be kept “private” is stated in an expertise, this will infringe upon the rights of a person if he lives or that of the relatives if he is dead. Sometimes the doctors are even forced to do that by judicial authority. Additionally, it has also been expected from the Forensic Medicine experts as well as the other doctors that they should first consider whether the ethical aspects of the case is present, and if so they should be so careful that legal interrogation should not be affected.In such cases, beside the personal solidarity, the efford given by the Society of Forensic Medicine Specialists (Experts), and the Turkish Medical Association and the others, whould be the most important determinant to solve the law based problems.Key words: Forensic medicine expertise, medical confidentiality
Keywords: forensic medicine expertise; medical confidentiality